Establishment of Regional-owned Food Business Entities as a Means to Eradicate Poverty and Increase Economic Growth - Maryunani Maryunani (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2021)
East Java is a large province in Indonesia with the population of more than 39 million people and has economic dominance in the agricultural sector. Huge agricultural sector resources in East Java have high comparative advantages. Regional-owned Food Business Entities is one of the strategic policies that become a bridge for the agricultural production sector with its market. It is hoped that the welfare of farmers can be improved and will have an impact on poverty reduction and economic growth in East Java. This study aims to: 1) Provide a description of the role of Regional-owned Food Business Entities and its prospects based on the perspective of farmers in East Java; 2) Analyze determinants of poverty and economic growth as the ultimate goal of food enterprises, through the agricultural sector approach. The method used in this study was panel data analysis with the data from Central Bureau of Statistics year 2010-2018. The results showed that almost all farmers supported the establishment of Regional-owned Food Business Entities with the prerequisites for price certainty that benefited farmers. Furthermore, the results of the estimation of multiple linear regressions in the poverty model and the economic growth model show that poverty is strongly influenced by the quality of human resources, as well as the economic growth model. Before realizing the Regional-owned Food Business Entities, benchmarking was recommended to find out best practices and feasibility studies in various aspects.